2013
DOI: 10.4134/bkms.2013.50.3.833
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Generalized Myers Theorem for Finsler Manifolds

Abstract: Abstract. In this note we establish a generalized Myers theorem under line integral curvature bound for Finsler manifolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Remark 2.1. If in the main theorem (Theorem 1.2) from [15] the function max is explicitly written, two statements are obtained. The one covers the first three items of the Bonnet-Myers theorem.…”
Section: Proof Of Theorem Amentioning
confidence: 99%
“…Remark 2.1. If in the main theorem (Theorem 1.2) from [15] the function max is explicitly written, two statements are obtained. The one covers the first three items of the Bonnet-Myers theorem.…”
Section: Proof Of Theorem Amentioning
confidence: 99%
“…The recent works have shown that some well-known results in Riemannian geometry have been extended to the Finsler setting. For examples in this scope, the reader is referred to [1][2][3] and references therein. In the Riemannian case, Ambrose [4] proved a compactness theorem by a condition on the integral of Ricci tensor along geodesics.…”
Section: Introductionmentioning
confidence: 99%
“…The recent works have shown that some results in Riemannian geometry have been extended to the Finsler setting. For example in this scope, the reader is referred to [1,2,3] and references therein.…”
Section: Introductionmentioning
confidence: 99%